Applying changes made during the COVID-19 pandemic to the future: trauma and orthopaedics. Issue 4 (2nd April 2021) - Umer, Hafiz Muhammad; Iqbal, Hafiz Javaid; Webb, Mark; Harrison, William James
Abstract : The NHS has made significant changes to practice and specialty training in trauma and orthopaedics as a result of the COVID-19 pandemic. This article looks at the positive and innovative changes along with lessons learnt, which could affect policies in a new challenging post-pandemic health service. At a national level, Public Health England, the British Orthopaedic Association and the Royal Colleges have issued a number of guidelines, which have evolved throughout the pandemic. Developing resilient rotas, virtual clinics, teleconsultations, webinar-based training and operating theatre reorganisation are just some examples of how collaborative working has led to positive changes, despite the huge challenges and hardships created by COVID-19. As we emerge from this crisis, the field of trauma and orthopaedics will need to prepare for the challenges of patient backlogs, neglected trauma and long waiting lists. A continuation of the innovative and collaborative working seen during the pandemic will be crucial to cope with the post-COVID-19 world of orthopaedics.